Formulasi Es Krim Nabati Berbasis Sari Kedelai dan Sari Sorgum dengan Pengental Xanthan Gum - Binardo A S Mawarno; Karina B Lewerissa (Universitas Pattimura, 2025)
The trend of low-fat consumption is not only limited to main meals, but also to desserts. Ice cream, which is usually made from milk, is replaced by plant-based ingredients that have low fat content but high protein such as soybean juice and sorghum juice. The purpose of this study was to obtain the best plant-based ice cream formulation with the ratio of soybean juice and sorghum juice and the use of xanthan gum as a stabilizer. The method in this study was a completely randomized design with two treatments, namely three ratios of soybean juice and sorghum juice (30:70; 50:50; 70:30) and two concentrations of xanthan gum (0.3% and 0.5%). Physical quality parameters observed were overrun and melting time, chemical quality parameters were proximate and sensory quality parameter which were taste, aroma, texture and overall acceptance. The three best treatments were then analyzed for functional value in the form of total phenolics, flavonoids and antioxidant activity. Statistical analysis used One Way ANOVA with Duncan's difference test. The results showed that the ratio of soybean juice and sorghum juice and the concentration of xanthan gum had a significant effect on physical, chemical and sensory parameters. Ice cream with a ratio of 30:70 and a concentration of 0.3% xanthan gum produced the highest overrun value of 39.71% but the longest melting time was obtained in the treatment of a ratio of 50: 50 and 0.5% xanthan gum concentration of 1005.98 seconds or 16.77 minutes. Based on functional analysis, the highest total phenolics, flavonoids and antioxidant activity were obtained in the ice cream treatment of soybean juice and sorghum juice 50:50 with the addition of xanthan gum as much as 0.5% as a stabilizer.